Involvement of the mitogen-activated protein (MAP) kinase signalling pathway in host cell invasion by Toxoplasma gondii - Robert-Gangneux F.; Creuzet C.; Dupouy-Camet J.; Roisin M.-P. (Parasite, 2000)
Little is known about signalling in Toxoplasma gondii, but it is likely that protein kinases might play a key role in the parasite proliferation, differentiation and probably invasion. We previously characterized Mitogen-Activated Protein (MAP) kinases in T. gondii lysates. In this study, cultured cells were tested for their susceptibility to Toxoplasma gondii infection after tachyzoite pretreatment with drugs interfering with AMP kinase activation pathways. Protein kinases inhibitors, i.e. genistein, R031-8220 and PD098059, reduced tachyzoite infectivity by 38 ± 4.5 %, 85.5 ± 9 % and 56 ± 10 %, respectively. Conversely, protein kinases activators, i.e. bombesin and PMA, markedly increased infectivity (by 202 ± 37 % and 258 ± 14 %, respectively). These results suggest that signalling pathways involving PKC and AAAP kinases play a role in host cell invasion by Toxoplasma.